Autonomic Arousal During Actigraphically Estimated Waking and Sleep in Male Veterans With PTSD. Issue 5 (October 2014) - Bertram, Franziska; Jamison, Andrea L.; Slightam, Cindie; Kim, Sunyoung; Roth, Heidi L.; Roth, Walton T.
<x xml:space="preserve">Abstract</x> Physiological hyperarousal is manifested acutely by increased heart rate, decreased respiratory sinus arrhythmia, and increased skin conductance level and variability. Yet it is uncertain to what extent such activation occurs with the symptomatic hyperarousal of posttraumatic stress disorder (PTSD). We compared 56 male veterans with current PTSD to 54 males who never had PTSD. Subjects wore ambulatory devices that recorded electrocardiograms, finger skin conductance, and wrist movement while in their normal environments. Wrist movement was monitored to estimate sleep and waking periods. Heart rate, but not the other variables, was elevated in subjects with PTSD equally during waking and during actigraphic sleep (effect sizes, Cohen's d, ranged from 0.63 to 0.89). The length of the sleep periods and estimated sleep fragmentation did not differ between groups. Group heart rate differences could not be explained by differences in body activity, PTSD hyperarousal symptom scores, depression, physical fitness, or antidepressant use.